Kepler rapidly rotating giant stars - Costa, A. D. (2015)
Rapidly rotating giant stars are relatively rare and may represent important stages of stellar evolution, resulting from stellar coalescence of close binary systems or accretion of substellar companions by their hosting stars. In the present Letter, we report 17 giant stars observed in the scope of the Kepler space mission exhibiting rapid rotation behavior. For the first time, the abnormal rotational behavior for this puzzling family of stars is revealed by direct measurements of rotation, namely from photometric rotation period, exhibiting a very short rotation period with values ranging from 13 to 55 days. This finding points to remarkable surface rotation rates, up to 18 times the rotation of the Sun. These giants are combined with six others recently listed in the literature for mid-infrared (IR) diagnostics based on Wide-field Infrared Survey Explorer information, from which a trend for an IR excess is revealed for at least one-half of the stars, but at a level far lower than the dust excess emission shown by planet-bearing main-sequence stars.